2016
DOI: 10.1038/srep37582
|View full text |Cite
|
Sign up to set email alerts
|

Isotope effect in superconducting n-doped SrTiO3

Abstract: We report the influence on the superconducting critical temperature Tc in doped SrTiO3 of the substitution of the natural 16O atoms by the heavier isotope 18O. We observe that for a wide range of doping this substitution causes a strong (~50%) enhancement of Tc. Also the magnetic critical field Hc2 is increased by a factor ~2. Such a strong impact on Tc and Hc2, with a sign opposite to conventional superconductors, is unprecedented. The observed effect could be the consequence of strong coupling of the doped e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
106
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(116 citation statements)
references
References 46 publications
(113 reference statements)
10
106
0
Order By: Relevance
“…Finally, the density of states ν in Eqs. (35) and (37) should be modified according to ν = ε F k F /2π 2 v 2 F . The decomposition of the Coulomb repulsion is more subtle.…”
Section: Possibility Of P-wave Pairingmentioning
confidence: 99%
“…Finally, the density of states ν in Eqs. (35) and (37) should be modified according to ν = ε F k F /2π 2 v 2 F . The decomposition of the Coulomb repulsion is more subtle.…”
Section: Possibility Of P-wave Pairingmentioning
confidence: 99%
“…For example, Raman scattering found that the hardening of the FE soft mode in the dilute metal is indistinguishably similar to what is seen in the insulator [21]. The anomaly in resistivity was found to terminate at a threshold carrier density (n * ), near which the superconducting transition temperature was enhanced [21] providing evidence for a link between superconducting pairing and ferroelectricity, a subject of present attention [22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 96%
“…If a ferroic phase transition can be suppressed to zerotemperature using a variable such as pressure or applied field, then the ordering is determined by quantum rather than thermal effects, resulting in exotic behavior even at finite temperatures. Such quantum criticality is well established for magnetic ordering, where it is believed to be responsible for example for heavy-fermion superconductivity, and has also recently been identified in ferroelectrics [90], where it is believed to be associated with the unconventional superconductivity in SrTiO 3 [91,92]. The concept of multiferroic quantum criticality ( Fig.…”
Section: Discussionmentioning
confidence: 97%